Bed Bugs and Blood-Sucking Conenose - Philip G. Koehler; Robero M. Pereira; M. Pfiester; Jeff Hertz (EDIS)
Revised! ENY-227, a 7-page illustrated fact sheet by P. G. Koehler, R. M. Pereira, M. Pfiester, and Jeff Hertz, describes these blood-sucking insects, their life cycles, and control methods. Includes new techniques for bed bug control and a table of insecticides labeled for bed bug control. Published by the UF Department of Entomology and Nematology, November 2008.